Optimizing Linearity and Sensitivity of 3D-Printed Diaphragms with Chirped FBGs in CYTOP Fibers - Leal-Junior, Arnaldo; Rocha, Helder R.O.; Theodosiou, Antreas; Frizera, Anselmo; Marques, Carlos Alberto F.; Kalli, Kyriacos; Ribeiro, Moises R.N. (My University, 2020)
We report the development of an optimization approach for diaphragm-embedded optical fiber sensors, which was applied on the pressure, force and liquid level assessment using chirped fiber Bragg gratings (CFBGs) inscribed in cyclic transparent optical polymer (CYTOP) fibers. The inscription was performed using the plane-by-plane method with a femtosecond laser, whereas the diaphragm optimization was performed through the multi-objective particle swarm optimization (MOPSO). The objective functions for the optimization were obtained from numerical simulation using the finite element method of diaphragms with different thickness and diameters. The MOPSO resulted in a set of solutions with thickness and diameter aiming the optimization of sensitivity and linearity of diaphragm-embedded CFBG sensors. Three configurations were chosen with different values sensitivity and linearity. Experimental analysis was performed in each configuration for temperature and pressure variations, where the results confirmed the different sensitivity and linearity levels for each chosen configuration. Two applications were analyzed for the proposed configurations with higher sensitivity and linearity: one for force estimation over a 200-N range and the other for sub-millimeter assessment of liquid level over a 50-cm range. In order to obtain a highly reliable and accurate system, a novel data integration method for chirped FBGs was proposed. In this case, the estimation of force, pressure or liquid level was performed considering the contributions of both wavelength shift and full width half maximum (FWHM) variations. The proposed approach resulted in error improvement of 60% for all cases and for all parameters analyzed.
Keywords: Chirped fiber Bragg gratings; Οptimization; Polymer optical fibers; Pressure sensors